2018
DOI: 10.1038/nri.2017.145
|View full text |Cite
|
Sign up to set email alerts
|

Improving immune–vascular crosstalk for cancer immunotherapy

Abstract: The vasculature of tumours is highly abnormal and dysfunctional. Consequently, immune effector cells have an impaired ability to penetrate into solid tumours and often exhibit compromised functions. Normalization of the tumour vasculature can enhance tissue perfusion and improve immune effector cell infiltration, leading to immunotherapy potentiation. However, recent studies, have demonstrated that stimulation of immune cell functions can also help to normalize tumour vessels. In this Opinion article, we propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
323
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(333 citation statements)
references
References 127 publications
(148 reference statements)
8
323
2
Order By: Relevance
“…ARDS induced by cytokine storm is reported to be the main reason for death of SARS-COV-2-infected patients (18). It is possible that in this setting, immunotherapy induces the release of a large amount of cytokines, which can be toxic to normal cells, including lung epithelial cells (19)(20)(21), and therefore lead to a more severe illness. However, in this study the number of patients with immunotherapy was too small; further research with a large case population needs to be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…ARDS induced by cytokine storm is reported to be the main reason for death of SARS-COV-2-infected patients (18). It is possible that in this setting, immunotherapy induces the release of a large amount of cytokines, which can be toxic to normal cells, including lung epithelial cells (19)(20)(21), and therefore lead to a more severe illness. However, in this study the number of patients with immunotherapy was too small; further research with a large case population needs to be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…MPM being refractory to chemotherapy and radiotherapy, the major translational interest is the identification of novel and promising therapeutic options, especially for the sarcomatoid and biphasic types. Several recent reviews have nicely summarized how the tumour-associated blood and lymphatic vasculature play an important role in avoiding tumour destruction, as well as the therapeutic opportunities to overcome this immune blockage (12)(13)(14)(15). Recent data from ongoing clinical trials presented in the iMig 2018 conference hold in Ottawa (Canada) pointed that, while immunotherapy remains promising in the treatment of a subset of mesothelioma patients, there is an urgent need to identify novel and better predictive markers of response (16).…”
Section: Discussionmentioning
confidence: 99%
“…S5e-g, but including only the 130 epithelioid samples. 13 Kaplan-Meier survival curve of the four regions highlighted in (a). c) Median (solid line) and 95% quantiles (filled shapes) of the expression level, measured in normalized read counts, of angiogenesis-related genes significantly associated with PC1: VEGFR1, VEGFR2, VEGFR3, VEGFC, and PDGFRB.…”
Section: Survival Analysismentioning
confidence: 99%
“…It is also well known that tumor cells create a challenging environment for the immune system characterized by hypoxia, low pH, high interstitial fluid pressure, and immune-inhibitory metabolites such as lactic acid 13,14 . The impaired perfusion capacity of tumor blood vessels by abnormal tumor vasculature create a highly hypoxic microenvironment, frequently resulting in immune suppression 15 . Recent studies have demonstrated that tumor hypoxia is negatively associated with the efficacy of immunotherapy and that the stimulation of immune cell functions with PD-1 and CTLA-4 blockade can also help to normalize tumor vessels 16,17 .…”
Section: Introductionmentioning
confidence: 99%